Linking soil fungi to bacterial community assembly in arid ecosystems. Issue 1 (24th February 2022) - Jiao, Shuo; Chu, Haiyan; Zhang, Baogang; Wei, Xiaorong; Chen, Weimin; Wei, Gehong
Abstract: Revealing the roles of biotic factors in driving community assembly, which is crucial for the understanding of biodiversity and ecosystem functions, is a fundamental but infrequently investigated subject in microbial ecology. Here, combining a cross‐biome observational study with an experimental microcosm study, we provided evidence to reveal the major roles of biotic factors (i.e., soil fungi and cross‐kingdom species associations) in determining soil bacterial biogeography and community assembly in complex terrestrial ecosystems of the arid regions of northwest China. The results showed that the soil fungal richness mediates the balance of assembly processes of bacterial communities, and stochastic assembly processes decreased with increasing fungal richness. Our results further suggest that the predicted increase in aridity conditions due to climate change will reduce bacterial α‐diversity, particularly in desert soils and subsurface layer, and induce more negative species associations. Together, our study represents a significant advance in linking soil fungi to the mechanisms underlying bacterial biogeographic patterns and community assembly in arid ecosystems under climate aridity and land‐use change scenarios. Abstract : Our findings revealed the major roles of biotic factors and aridity in shaping the bacterial landscapes and mediating the community assembly in complex terrestrial ecosystems. Soil fungal richness mediates the balance of assembly processes of soil bacterial communities, with stochastic assembly processes decreasing along with an increase in fungal richness. Increased aridity conditions due to climate change could reduce the bacterial α‐diversity, with more negative effects in desert soils and subsurface layers, and induce more antagonistic or competitive biological interactions. Highlights: Soil fungal richness mediates the bacterial community assembly. Stochastic assembly processes decreased with increasing fungal richness. Increase in aridity reduced bacterial α‐diversity.